2018
DOI: 10.1530/eje-18-0185
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting FC-fusion rhGH (GX-H9) shows potential for up to twice-monthly administration in GH-deficient adults

Abstract: GX-H9 has the potential for up to twice-monthly administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…HyTropin (Produced by Genexine and Handok of South Korea) is fused to the Fc-domain of immunoglobulin. A Phase II study in Europe demonstrated efficacy and apparent safety in adults with GH deficiency ( 187 ).…”
Section: Non-covalent Albumin Binding Ghmentioning
confidence: 99%
“…HyTropin (Produced by Genexine and Handok of South Korea) is fused to the Fc-domain of immunoglobulin. A Phase II study in Europe demonstrated efficacy and apparent safety in adults with GH deficiency ( 187 ).…”
Section: Non-covalent Albumin Binding Ghmentioning
confidence: 99%
“…A Phase 2 randomized, openlabel study was conducted in 16 endocrinology centers in Europe and Korea among 45 adult participants with growth hormone deficiency. With twice-monthly administration, the drug demonstrated comparable efficacy and acceptable tolerability without significant immunogenicity (35). The manufacturer is planning a Phase 3 study with a longer treatment period and more patients in the United States.…”
Section: Growth Hormone Fusion Proteinsmentioning
confidence: 99%
“…Furthermore, the rest of the Fc protein of HL2351 is engineered from the human immunoglobulin G4, which is less susceptible to antibody‐dependent cellular cytotoxicity and complement‐dependent cytotoxicity than other antibody isotypes . The hybrid Fc‐fusion technology has been successfully applied to other endogenous peptides and proteins such as human growth hormone and erythropoietin to extend their short half‐lives. Because the role of IL‐1ra has is well known in the blocking of the signal mediated through the IL‐1 receptor, HL2351 could be a more practical, if not a better, option than a new monoclonal antibody with a new epitope for the IL‐1 receptor, which needs to be newly developed from scratch.…”
Section: Introductionmentioning
confidence: 99%